The United States, Iran’s Revolution, and the USSR Communist Phantom: The Linchpins that Triggered the Emergence of the Moroccan “Modern” Armed Forces from 1979 to 1982? - Teixeira, Jorge (The Journal of US-Africa Studies, 2023)
The ghost of the USSR was one of the most important weapons used throughout the Cold War. This phantom made the US act almost immediately, helping his allies or to outmanoeuvring his political opponents. In the case of Iran, it made the US try to solve a deep social/economic problem by showering Iran with military and economic aid, which would prove to be fatal. Moroccan king Hassan II, an expert and savvy political manipulator, would use his position as a US proxy agent to manoeuvre in the shadows within the Arab-speaking world and Africa. This position came to be in full effect when Morocco invaded Western Sahara, with the confidence that it would be a short affair. This proved to be difficult, almost impossible, as a short war became a long one. However, when in 1979, Iran, a stable political ally of the US, plummeted there were a shift in the US politics. The very public rhetoric branding Polisario as a communist agent proved to be a stepping stone into reverting an almost lost war into a stalemate. The US, not wanting a replication of what happened in Iran to happen in Morocco, changed its policies. Polisario was now seen as a threat to the Moroccan Regime. Therefore, trying to prevent possible proxy problems such as internal un-ruling and uprises that could lead to the fall of the kingdom, the US used the Iranian solution: military and economic aid. Keywords: Morocco, USSR, US, Iran Revolution, Cold War, Weapons Trade.